Mapping of groundwater quality using GIS technique in the east coast of Tamilnadu state and Pondicherry union territory, India - Kumaravel, S.; Gurugnanam, B.; Bagyaraj, M.; Venkatesan, S.; Suresh, M.; Chidambaram, S.; Jeyavel Rajakumar, T.; Gnanachandrasamy, Gopalakrishnan (International Journal of Advanced Geosciences, 2014)
The objective of this study is to determine temporal and spatial changes in groundwater quality and sources of contamination. An attempt has been made in the present study to elucidate the quality of the groundwater in terms of physical and chemical parameters in the post and pre monsoon season in the east coast of Tamilnadu state and Pondicherry Union Territory. Geologically, the study area consists of alluvium, Cuddalore sandstone and charnockite. 37 groundwater samples were collected from bore wells and analyzed for pH, TDS, Ca+, Mg+, Na+, K+, Cl-, HCO3-, SO4- and F-. The analyzed values were evaluated and compared with World Health Organization (2004) for drinking water. It was observed that, Ca+, Mg+, Na+, K+, Cl-, SO4- and F- are within the acceptable limit for drinking purposes in both the seasons except few sample locations. To identify the suitable zones of drinking water, overlay analyses were carried out using ArcGIS and classified as good, medium and poor zones for both the seasons. The zone of good quality of the groundwater for post and pre monsoon season in the study area was 118.93 km2 and 88.39 km2 respectively. Keywords: Spatial Changes, Groundwater Quality, Chemical Parameters, Drinking Purposes, ArcGIS.